An Immunity-Related Gene Model Predicts Prognosis in Cholangiocarcinoma - Guo, Han; Qian, Yihan; Yu, Yeping; Bi, Yuting; Jiao, Junzhe; Jiang, Haocheng; Yu, Chang; Wu, Hailong; Shi, Yanjun; Kong, Xiaoni (Frontiers in Oncology, 2022)
The prognosis of patients with cholangiocarcinoma (CCA) is closely related to both immune cell infiltration and mRNA expression. Therefore, we aimed at conducting multi-immune-related genes to improve the prediction of CCA recurrence. Immune-related genes were selected from Gene Expression Omnibus (GEO), The Cancer Genome Atlas (TCGA), and Immunology Database and Analysis Portal (ImmPort). The least absolute shrinkage and selection operator (LASSO) regression model was used to establish the multi-gene model that was significantly correlated with the recurrence-free survival (RFS) in two test series. Furthermore, compared with single-gene, clinical characteristics, tumor immune dysfunction and exclusion (TIDE), and tumor inflammation signature (TIS), the 8-immune-related differentially expressed genes (8-IRDEGs) signature had better prediction value. Besides, the high-risk subgroup had a lower density of B cell, plasma, B cell naïve, CD8+ T cell, CD8+ T cell naïve, and CD8+ T cell memory infiltration, more severe immunosuppression, and higher mutation counts. In conclusion, the 8-IRDEGs signature was a promising biomarker for distinguishing the prognosis, the molecular and immune characteristics of CCA, and could be beneficial to the individualized immunotherapy for CCA patients.